The effects of fluorene-9-bisphenol on female zebrafish (Danio rerio) reproductive and exploratory behaviors. (August 2019) - Mi, Ping; Zhang, Qiu-Ping; Zhang, Shu-Hui; Wang, Chao; Zhang, Shao-Zhi; Fang, Yong-Chun; Gao, Jian-Zhao; Feng, Dao-Fu; Chen, Dong-Yan; Feng, Xi-Zeng
Abstract: Endocrine disruptor chemicals induce adverse effects to animals' development, reproduction and behavior in environment. We investigated the effects of fluorene-9-bisphenol (BHPF), one substitute of bisphenol A, on courtship behavior and exploratory behavior of adult zebrafish. Customized apparatus was used to evaluate courtship behavior. The result showed that the male spent less time with BHPF and anti -oestrogenic fulvestrant (FULV) treated female in region of approaching (ROA). Courtship index between BHPF-exposed female and male decreased. The body orientation of BHPF- and FULV-exposed female to male decreased. Furthermore, BHPF exposure downregulated the expression of genes related to estrogen receptor, steroidogenesis and upregulated oxidative stress related genes. It indicated that BHPF exposure interfered the preference of male and female in courtship, and induced detrimental effects on reproduction. BHPF treatment decreased locomotor activity and time spent in top, increased freezing bouts, and induced anxiety/depression-like behavior. The tyrosine hydroxylase in brain decreased under BHPF exposure. Here we showed the potential adverse effects of BHPF on reproduction and exploratory behaviors. Graphical abstract: Image 1 Highlights: Male spent less time with BHPF treated female in ROA. BHPF decreased the courtship index between female and male. BHPF downregulated the expression of genes related to ER and steroidogenesis. BHPF induced anxiety/depression-like behavior and reduced TH level.